Developing dendritic cell-based therapies to condition immune responses to novel oncogenic proteins and stem cells. Issue 5 (September 2009) - Sharma, Anupama; Czerniecki, Brian J
Cancer vaccines have been disappointing when utilized as stand-alone therapy, especially in late disease settings. However, recent clinical studies in prostate cancer have suggested that dendritic cellular (DC) vaccines may impact patient survival, reviving the notion that cancer vaccines can impact established cancer. In this review we will highlight the advances that have been made in the development of DC-based therapies activated by Toll-like receptor agonists with the capacity to condition toward strong Th1 cellular responses, through the production of cytokines and chemokines, and a capacity to induce apoptosis of tumor cells. Used in early cancer settings, these DCs induce clinically effective immune responses, thus shifting the emphasis toward using these cells earlier in the disease process. We will also discuss targeting novel molecules and cancer stem cells that can eliminate cells with high metastatic potential, moving DC-based therapies into mainstream cancer therapy.